Pitx2 is a useful marker of midgut‐derived neuroendocrine tumours – an immunohistochemical study of 224 cases. Issue 6 (22nd September 2022) - Soukup, Jiri; Manethova, Monika; Faistova, Hana; Krbal, Lukas; Vitovcova, Barbora; Hornychova, Helena; Drugda, Jan; Cesak, Tomas; Netuka, David; Gabalec, Filip; Ryska, Ales
Abstract : Pitx2 is a transcription factor responsible for establishment of the right–left axis and development of the gut and pituitary. In mouse embryos, Pitx2 is expressed in the greater curvature of the stomach and midgut. Previously, Pitx2 was studied in pituitary neuroendocrine tumours but not in other NETs. Pitx2 expression was immunohistochemically assessed in whole sections and tissue microarrays in a cohort of 224 neuroendocrine neoplasms, and was analysed in 29 cases. The cohort included 18 cauda equina NETs, 38 paragangliomas, 98 cases of primary visceral NETs from different organs, 23 metastases of visceral NETs and 47 neuroendocrine carcinomas (NECs). Pitx2 expression was observed in 29.5% (29 of 98) NETs and 14.9% (7 of 47) NECs, but was not observed in any paraganglioma or cauda equina NET. Pitx2 was observed only in tumours of midgut‐derived organs, including the small intestine (100%, 20 of 20), appendix (88.9%, eight of nine) and large intestine (9.1%, one of 11 – only caecal NET). The NETs of remaining locations were negative. Pitx2 was 96.7% sensitive and 100% specific for NETs of midgut origin. In NECs, Pitx2 positivity was observed in goblet cell adenocarcinoma (75%, three of four), medullary thyroid carcinoma (42.9, three of seven) and one Merkel cell carcinoma (25%, one of four). In metastatic NETs, Pitx2 was observed in all the tumours originating in the small intestine ( n  = 17) or caecum ( n  = 1). No positivity was observed in tumours from other locations (four pancreas, one lung). We observed no correlation between immunoreactivity and mRNA expression. Thus, Pitx2 immunohistochemistry can be helpful in assessing the midgut origin of NETs. Abstract :